Experimental analysis of ethanol dual-fuel combustion in a heavy-duty diesel engine: An optimisation at low load. (1st March 2016) - Pedrozo, Vinícius B.; May, Ian; Dalla Nora, Macklini; Cairns, Alasdair; Zhao, Hua
Highlights: Dual-fuel combustion offers promising results on a stock heavy-duty diesel engine. The use of split diesel injections extends the benefits of the dual-fuel mode. Ethanol–diesel dual-fuel combustion results in high indicated efficiencies. NOx and soot emissions are significantly reduced. Combustion efficiency reaches 98% with an ethanol energy ratio of 53%. Abstract: Conventional diesel combustion produces harmful exhaust emissions which adversely affect the air quality if not controlled by in-cylinder measures and exhaust aftertreatment systems. Dual-fuel combustion can potentially reduce the formation of nitrogen oxides (NOx) and soot which are characteristic of diesel diffusion flame. The in-cylinder blending of different fuels to control the charge reactivity allows for lower local equivalence ratios and temperatures. The use of ethanol, an oxygenated biofuel with high knock resistance and high latent heat of vaporisation, increases the reactivity gradient. In addition, renewable biofuels can provide a sustainable alternative to petroleum-based fuels as well as reduce greenhouse gas emissions. However, ethanol–diesel dual-fuel combustion suffers from poor engine efficiency at low load due to incomplete combustion. Therefore, experimental studies were carried out at 1200 rpm and 0.615 MPa indicated mean effective pressure on a heavy-duty diesel engine. Fuel delivery was in the form of port fuel injection of ethanol and common rail direct injection of diesel. The objective was to improve combustion efficiency, maximise ethanol substitution, and minimise NOx and soot emissions. Ethanol energy fractions up to 69% were explored in conjunction with the effect of different diesel injection strategies on combustion, emissions, and efficiency. Optimisation tests were performed for the optimum fuelling and diesel injection strategy. The resulting effects of exhaust gas recirculation, intake air pressure, and rail pressure were investigated. The optimised combustion of ethanol ignited by split diesel injections resulted in higher net indicated efficiency when compared to diesel-only operation. For the best emissions case, NOx and soot emissions were reduced by 65% and 29%, respectively. Aftertreatment requirements that are generally associated with cost and fuel economy penalties can be minimised. Combustion efficiency of 98% was achieved at the expense of higher NOx emissions.